Peran ekstrakurikuler pencak silat dalam membentuk nilai-nilai moderasi beragama siswa smpn 8 kota blitar - Aqma, Tahajudi (Maliki Interdisciplinary Journal, 2026)
Character education is important in the world of education. In realizing this, there are values of moderation that can achieve character education. Therefore, this study aims to explore the influence of pencak silat extracurricular activities in shaping religious moderation values at SMPN 8 Blitar City. This study also aims to examine the role of pencak silat extracurricular activities in shaping students' values of religious moderation, motivated by the urgency of instilling tolerance and anti-violence in the school environment. The study uses a mixed method approach with an explanatory sequential design. The quantitative sample involved 38 students participating in extracurricular activities (total sampling), analyzed using Simple Linear Regression. Qualitative data was obtained through in-depth interviews with coaches and students. Descriptive results show that students' religious moderation levels are in the Very Good category. Regression tests prove that there is a significant and positive role. Qualitatively, the internalization of values occurs through the habit of ethical rituals that foster solidarity and the philosophy of self-control or anti-violence taught by coaches, as well as the preservation of local culture. Conclusion: Pencak silat extracurricular activities are proven to be effective as a contextual and experience-based medium in shaping students' moderate character. This makes pencak silat a relevant character-building model to support religious moderation programs in schools.